2020
DOI: 10.1007/s10460-020-10145-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the public attitudinal acceptance of digital farming technologies: a nationwide survey in Germany

Abstract: The magnitude of public concerns about agricultural innovations has often been underestimated, as past examples, such as pesticides, nanotechnology, and cloning, demonstrate. Indeed, studies have proven that the agricultural sector presents an area of tension and often attracts skepticism concerning new technologies. Digital technologies have become increasingly popular in agriculture. Yet there are almost no investigations on the public acceptance of digitalization in agriculture so far. Our online survey pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 90 publications
(162 reference statements)
4
40
0
1
Order By: Relevance
“…Nevertheless, the positive direction of the path coefficient shows that a positive public discussion about AI and digitalization in agriculture could increase farmers' acceptance of AI systems. In line with this, a representative survey by Pfeiffer et al (2021) shows that the population remains alienated from agriculture and currently has a low level of knowledge about modern production processes. Digital technologies are only evaluated positively among consumers after having received an explanation of their potential.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Nevertheless, the positive direction of the path coefficient shows that a positive public discussion about AI and digitalization in agriculture could increase farmers' acceptance of AI systems. In line with this, a representative survey by Pfeiffer et al (2021) shows that the population remains alienated from agriculture and currently has a low level of knowledge about modern production processes. Digital technologies are only evaluated positively among consumers after having received an explanation of their potential.…”
Section: Discussionmentioning
confidence: 81%
“…To date, public knowledge of agricultural production processes is rather limited. Due to the alienation of society from food production, the media increasingly shape ideas about agricultural production processes (Pfeiffer et al, 2021). On the one hand, an idyllic image of agricultural production is conveyed through media representations (Albersmeier et al, 2008).…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…There is a need to consider how this resistance to such engagement may play out specifically in digital agriculture, as there has been little scientific inquiry in this area to date, despite emerging evidence to suggest it will be of increasing importance for the future integration and acceptance of these technologies at market level. A recent survey of the German general population found relatively high public support for funding of research for digital farming livestock technologies, but also identified a growing disconnect between the general public and the agricultural sector which led to emotionally driven concerns about these technologies (Pfeiffer, Gabriel, and Gandorfer 2021). Given that societal reactions to modern livestock practices often generate much debate (Boogaardt et al 2011), the means and extent to which the general public are engaged in both conversations and innovation processes is an area of inquiry deserving of more reflection.…”
Section: Discussionmentioning
confidence: 99%
“…Results in different European countries show that there is a general positive reaction to the potential of farming technologies, through enhancing health and welfare of the animals and addressing environmental issues (Krampe et al, 2021;Pfeiffer, Gabriel and Gandorfer, 2021), but other citizens' attitudes can be negative (Giersberg and Meijboom, 2021). When presented with pictures of such digital systems, respondent's attitudes changed to a negative association and criticism (Pfeiffer, Gabriel and Gandorfer, 2021), and many fears are present including the intense industrialization of livestock farming and data misuse and criminality (Krampe et al, 2021). Such studies shows that the promising aspects of precision livestock farming cannot neglect the societal attitude towards this digitalization, and that such surveys can contribute to the development of PLF technologies.…”
Section: Impact Of Precision Livestock Farming On Society and The Planetmentioning
confidence: 99%